186k views
11 votes
I need help for 2,3, and 4

I need help for 2,3, and 4-example-1

1 Answer

11 votes

Answer:

2.

x = -1 , y = 4

3.

x = 7, y = -1

4.

x = 1, y = 2

Explanation:

2. 6x + 2y = 2, -3x - 4y = -13

3. 4x + 8y = 20, -4x + 2y = -30

4. y = -3x + 5, 5x - 4y = -3

2.

We have to determine the solutions of this system of equations, basically look for x and y. First, let's solve through elimination.

6x + 2y = 2

-3x - 4y = -13

Multiply the second equation by 2 :

6x + 2y = 2

-6x - 8y = -26

Add the equations and solve for y :

-6y = -24

Divide both sides by -6 :

y = 4

Now that we have found y, we can substitute 4 in y of the first equation :

6x + 2(4) = 2

6x + 8 = 2

Subtract 8 from both sides :

6x = -6

Divide both sides by 6 :

x = -1

3.

4x + 8y = 20

-4x + 2y = -30

We are asked to solve in elimination style, do as followed :

4x + 8y = 20

-4x + 2y = -30

Add and solve for y :

10y = -10

Divide 10 from both sides to get y alone :

y = -1

Now that we know y, we can substitute it into the first equation :

4x + 8(-1) = 20

4x - 8 = 20

Add 8 to both sides :

4x = 28

Divide 4 from both sides :

x = 7

4.

y = -3x + 5

5x - 4y = -3

We are asked to solve with substitution :

Since the first equation has y alone, we can replace it with y in the second equation :

5x - 4(-3x + 5) = -3

Distribute :

5x + 12x - 20 = -3

Combine like terms :

17x - 20 = -3

Add 20 to both sides :

17x = 17

Divide 17 from both sides :

x = 1

Now that we know y, we can substitute x in the first equation with 1 :

y = -3(1) + 5

y = -3 + 5

y = 2

User Archgoon
by
4.7k points